Characterization of (2+2) Macrocyclic Compounds of Co(II) and Ni(II) Derived from 2,6-Diacetyl Pyridine and Phenylene Diamines - Kumar, R.N.; Chauhan, N.M.; Das, A.K.; Singh, S.K. (Asian Journal of Chemistry, 2010)
A number of complexes of the types [ML1]X2, [ML2]X2 [M = Co(ll) or Ni(II); X = Cl- Br-, NO3-, OAc- ; L1 = Bis(2,6-diacetylpyridine-1,3- diamine) and L2 = Bis(2,6-diacetylpyridine-1,4-diamine)] have been synthesised and characterised.